Infant dietary exposure to dioxin-like polychlorinated biphenyls (dlPCBs), polybrominated and mixed halogenated dibenzo-p-dioxins and furans (PBDD/Fs and PXDD/Fs) in milk samples of lactating mothers in Accra, Ghana. (January 2021) - Bruce-Vanderpuije, Pennante; Megson, David; Jones, Gareth Rhys; Jobst, Karl; Reiner, Eric; Clarke, Edith; Adu-Kumi, Sam; Gardella, Joseph A.
Abstract: In this study, polybrominated and mixed halogenated dibenzo-p-dioxins and furans (PBDD/Fs and PXDD/Fs), and dioxin-like polychlorinated biphenyls (dlPCBs) were quantified in 24 human milk samples of first-time lactating mothers from Greater Accra region in Ghana. The aims of the study were to determine the concentrations and toxic equivalent concentrations of PBDD/F, PXDD/F and dlPCBs in human milk, and to estimate an infant's daily intake. The samples were analysed for 12 dioxin-like PCBs, 7 congeners of 2, 3, 7, 8-polybrominated dibenzo-p-dioxins and furans (PBDD/Fs), and 7 congeners of 2, 3, 7, 8-mixed halogenated dioxins and furans (PXDD/Fs, where X = Br/Cl). The mean concentrations in human milk ranged from 0.15 to 212.9 pg/g lipid for dlPCB congeners (mean TEQ: 1.67 pg WHO2005 -TEQ/g lipid). Lesser concentrations for 2, 3, 7, 8-PXDD/Fs (and PBDD/Fs congeners) ranged between <0.01–1.67 pg/g lipid, with a total mean tentative TEQ of 0.56 pg WHO2005 -TEQ/g lipid. For an infant of average weight 7 kg, consuming an estimated volume of 600 mL human milk, the estimated average daily intake of dlPCBs in 21 human milk samples was 4.95 pg TEQ/kg bw/day; contributions from dlPCBs, PXDD/Fs and PBDD/Fs resulted in an average estimated daily intake of 6.56 pg TEQ/kg bw/day. The results obtained in this study, although lower than infant dietary intake estimates in human milk from industrialized countries, exceeded the recommended safety standards of 1 pg TEQ/kg bw/day and 1–4 pg TEQ/kg bw/day from the Agency for Toxic Substances and Disease Registry (ATSDR) and the World Health Organization (WHO), respectively. Highlights: First study on Ghanaian infant dietary intake of PBDD/Fs, PXDD/Fs from human milk. Average daily intake of DLCs exceeded WHO recommended safety standards. Concentrations dlPCBs ≫ PBDD/Fs > PXDD/Fs. Human milk TEQ concentrations: lower than estimates from industrialized countries.